2022
DOI: 10.1002/adom.202200516
|View full text |Cite
|
Sign up to set email alerts
|

Orthorhombic Non‐Perovskite CsPbI3 Microwires for Stable High‐Resolution X‐Ray Detectors

Abstract: Direct conversion X-ray detectors operate by directly converting X-ray photons into an electrical signal, while indirect conversion detectors (also called scintillators) first convert X-ray photons to visible light. Subsequently, this light is converted to an electrical signal using visible light detectors. Direct conversion detectors are simpler in configuration and offer higher spatial resolution than scintillators. [2] Among traditional semiconductors, amorphous selenium (a-Se), [3] and Cd 1−x Zn x Te (CZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…Therefore, in this study, MAPbBr 3 was chosen as the most actively studied bromide perovskite. The linear absorption coefficient of MAPbBr 3 as a function of X-ray energy can be calculated from the composition and atomic cross-section of the constituent elements (Figure a). The reciprocal of the linear absorption coefficient, known as the attenuation coefficient, represents the thickness of the layer required to absorb 63% of the incident X-ray intensity and is also shown in the same graph. To effectively absorb high-energy (60–120 keV) X-ray photons used in medical scan, it is necessary to have a MAPbBr 3 thickness of at least 0.5–1.5 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in this study, MAPbBr 3 was chosen as the most actively studied bromide perovskite. The linear absorption coefficient of MAPbBr 3 as a function of X-ray energy can be calculated from the composition and atomic cross-section of the constituent elements (Figure a). The reciprocal of the linear absorption coefficient, known as the attenuation coefficient, represents the thickness of the layer required to absorb 63% of the incident X-ray intensity and is also shown in the same graph. To effectively absorb high-energy (60–120 keV) X-ray photons used in medical scan, it is necessary to have a MAPbBr 3 thickness of at least 0.5–1.5 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Kundu et al reported solution-grown δ-CsPbI 3 microwires for X-ray detection with high performance. [195] Specifically, the ITO/δ-CsPbI 3 www.advancedsciencenews.com microwires/ITO device exhibited one of the lowest detectable X-ray dose rates at 33.3 nGy air s −1 , resulted from the exceptionally low dark current density of 12 pA mm −2 . Meanwhile, the microwires-based X-ray detector demonstrated excellent operational stability under a high continuous X-ray dose rate of 45 Gy air s −1 .…”
Section: Photodetectorsmentioning
confidence: 99%
“…However, it is currently challenging to produce millimeter-thick large-area films using traditional deposition techniques or blade coating. On the other hand, the production of perovskite single-crystal detectors is restricted by immature technology and high costs, particularly for the low-dimensional perovskite crystals. , Due to its highly tunable nature and cost-effective production processes, the fabrication of perovskite wafers represents a simple and commercially viable approach for developing X-ray detectors . This method can be easily scaled up using molds or patterns, making it preferable to using single crystals (SCs).…”
Section: Introductionmentioning
confidence: 99%